Complete Convergence for Weighted Sums of Negatively Superadditive Dependent Random Variables (Journal of Mathematical Study, 2014)
Let $\{X_n,n≥1\}$ be a sequence of negatively superadditivedependent (NSD, in short) random variables and $\{a_{nk}, 1\leqk≤ n, n≥1\}$ be an array of real numbers. Under some suitableconditions, we present some results on complete convergence forweighted sums $\sum_{k=1}^na_{nk}X_k$ of NSD random variables byusing the Rosenthal type inequality. The results obtained in thepaper generalize some corresponding ones for independent randomvariables and negatively associated random variables.
Keywords: Negatively superadditive dependent random variables; Rosenthal type inequality; complete convergence.